SOCIAL MEDIA INSECURITIES IN EVERYDAY LIFE AMONG YOUNG ADULTS – AN ETHNOGRAPHY OF ANONYMOUS JODEL DISCLOSURES - Larsen, Malene Charlotte (AoIR Selected Papers of Internet Research, 2020)
This paper analyzes what makes young adults feel insecure when they use social media in everyday life as a means to socialize and connect with peers. The analysis is based on a two-year online ethnography (Hine, 2015) conducted on Jodel, an anonymous location based social media app popular among young adults across Europe. The paper focuses on Jodel users’ anonymous disclosures about their social media related insecurities – shedding light on discourses related to social media practices that are often hidden or neglected in interview studies. The analysis finds that it is often the affordances of the social media platforms (Bucher & Helmond, 2018) or changes in the design of apps such as Snapchat, Instagram or Tinder that lead to feelings of insecurity or uncertainty in relational maintenance or in the forming of new relationships. Thus, the codes of everyday actions become unclear and different expectations as to the affordances of social media platforms result in diffuse interaction orders (Goffman, 1983) in various situations. Put in other words: Because of the platforms, young adults sometimes find it difficult to know why peers behave like they do online resulting in unfounded worries and feelings of insecurity.